2014
DOI: 10.1103/physreve.90.042142
|View full text |Cite
|
Sign up to set email alerts
|

Flux rectification in the quantumXXZchain

Abstract: Thermal rectification is the phenomenon by which the flux of heat depends on the direction of the flow. It has attracted much interest in recent years due to the possibility of devising thermal diodes. In this paper, we consider the rectification phenomenon in the quantum XXZ chain subject to an inhomogeneous field. The chain is driven out of equilibrium by the contact at its boundaries with two different reservoirs, leading to a constant flow of magnetization from one bath to the other. The nonunitary dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
132
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(136 citation statements)
references
References 37 publications
4
132
0
Order By: Relevance
“…We can point out two mechanisms for enhancing current rectification: (i) rectification coefficient R → 1 in thermodynamic limit n → ∞, at fixed large gradient f/(n − 1), for any nonzero anisotropy (interaction) = 0, as a result of our asymptotic current formula; (ii) for resonant field (gradient) values where our asymptotic analysis fails, the current is of higher order in 1/f for one direction of the field f than in the other. This clearly yields rectification coefficient R → 1 even at fixed finite size n. Note that there is no rectification effect in the noninteracting chains = 0, in agreement with [33]. Our analysis can be used also to reveal large anisotropy asymptotics 030103-4…”
supporting
confidence: 79%
“…We can point out two mechanisms for enhancing current rectification: (i) rectification coefficient R → 1 in thermodynamic limit n → ∞, at fixed large gradient f/(n − 1), for any nonzero anisotropy (interaction) = 0, as a result of our asymptotic current formula; (ii) for resonant field (gradient) values where our asymptotic analysis fails, the current is of higher order in 1/f for one direction of the field f than in the other. This clearly yields rectification coefficient R → 1 even at fixed finite size n. Note that there is no rectification effect in the noninteracting chains = 0, in agreement with [33]. Our analysis can be used also to reveal large anisotropy asymptotics 030103-4…”
supporting
confidence: 79%
“…Note that, from Eq. (20), in the steady state and in the presence of a homogeneous magnetic field we have F = F XXZ + B J , with F XXZ an even function of f , as argued above, and J an odd function of f (the spin current direction is determined by the direction of the magnetization imbalance). Hence, the energy rectification (change in the magnitude of F as we invert the baths) is clear: if we invert the sign of f , only one term of F changes the sign.…”
Section: Currents and Preliminary Resultsmentioning
confidence: 99%
“…In Ref. [20], the authors show the existence of spin current rectification in the homogeneous XXZ chain (with α i,i+1 = α and ∆ i,i+1 = ∆, ∀i) under an inhomogeneous, linearly graded, magnetic field for small chains, up to N = 7. Moreover, they show the vanishing of rectification as ∆ → 0, i.e., for the XX chain, and emphasize the correspondence to the well known result of absence of (energy) rectification in classical harmonic chains: written in terms of fermionic creation and annihilation operators, the XX model contains only quadratic terms, whereas the XXZ model involves also a quartic term which is proportional to ∆.…”
Section: Steady State Computation: Solutions and Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Such equations, which we shall henceforth refer to as LMEs (also frequently called boundarydriven master equations), are typically accurate when the dissipation rates are larger than the interaction between subsystems. Due to their computational simplicity, they have been extensively employed over the last two decades in the study of transport in non-equilibrium quantum systems [55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73].It turns out, however, that the nonlocal terms neglected in the LME may still lead to non-thermal steadystates [74] and play a significant role if the heat exchanges are small, even for weakly interacting parts. As a consequence, it has been found that LMEs may lead to apparent thermodynamic inconsistencies, as pointed out recently by Levy and Kosloff [75].…”
mentioning
confidence: 99%